SISTEM MANAJEMEN PRAKTEK KERJA LAPANGAN BERBASIS WEB DI PT. TELKOM SURABAYA - Juliyansah Rohmatulloh; Ahsani; Totok mulyono (Jurnal Teknologi dan Terapan Bisnis, 2022)
In the history of human life, science is one of the bridges of mankind to perfection. The human tendency to kehanifan makes it always move forward to become a better creation day by day. One of the dynamic movements of humans is reflected in the development of technology and information that helps human work to be more effective and efficient. Based on this reason, the author developed a Web-Based Application System Management Application at PT. Telkom Surabaya. The author analyzes and designs the infrastructure of applications that are built using the waterfall method, with stages of analysis including analysis of system weaknesses and system requirements analysis, design or design which includes modeling systems using the UML method and interface design, code and testing using PHP as a programming language and My SQL as a database manager, continuing at the stage of implementation and maintenance. From this study the application of a Web-Based Field Work Management System application data that will be processed by the application produces reports on street vendor data in graphical form.